N-acetyl glucosamine improves intestinal mucosal barrier function in rat - Liu, Yanxia; Xu, Weiwei; Liu, Lei; Guo, Linming; Deng, Yu; Liu, Junkang (Bangladesh Journal of Pharmacology, 2012)
Our study investigated the effect of N-acetylglucosamine (GlcNAc) on the intestinal mucosal barrier function in rats. Rats were randomly assigned into normal control group, diarrhea-predominant irritable bowel syndrome (IBS-D) group and GlcNAc group. IBS-D was introduced into the IBS-D group without any treatment. The GlcNAc group were treated with GlcNAc. Microvilli and tight junctions of intestinal epithelial cells were detected. The D-lactic acid level and diamine oxidase (DAO) activity in the serum were determined. Compared with normal rats, microvilli were sparsely distributed on the intestinal epithelial cells, the tight junction gap also widened, and D-lactic acid level and DAO activity were significantly higher in the IBS-D group. After GlcNAc treatment, the microscopic structure of the intestinal mucosa became largely normal, and the level of D-lactic acid and the DAO activity were lowered. In conclusion, GlcNAc can effectively improve the intestinal mucosal barrier dysfunction, perhaps through enhancing the cellular metabolism.